2015
DOI: 10.1016/j.amepre.2014.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Physical Activity Outcomes in Latinas in the Seamos Saludables Trial

Abstract: Background Physical activity interventions designed for Latinas have shown short-term behavior change, but longer-term change and maintenance is rarely measured. Purpose To assess physical activity change at 12 months, following 6-month tapered completion of a randomized controlled trial of a physical activity intervention for Latinas. Methods Two hundred sixty-six underactive (<60 minutes/week physical activity) Latinas were randomized to an individually tailored, culturally and linguistically adapted phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…19,20 Adult women (aged 18 to 65 years) who self-identified as Hispanic or Latina, could read and write in Spanish, and were underactive (<60 minutes of MVPA/week) were recruited for participation in the trial. A total of 132 participants (mean age = 41.6 + 10.1 years; mean body mass index = 25.6+4.3 kg/m 2 ) were randomized to a 12 month print-based physical activity intervention.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 Adult women (aged 18 to 65 years) who self-identified as Hispanic or Latina, could read and write in Spanish, and were underactive (<60 minutes of MVPA/week) were recruited for participation in the trial. A total of 132 participants (mean age = 41.6 + 10.1 years; mean body mass index = 25.6+4.3 kg/m 2 ) were randomized to a 12 month print-based physical activity intervention.…”
Section: Methodsmentioning
confidence: 99%
“…20 The primary findings of the Seamos Saludables study found participants randomized to the Print intervention significantly increased self-reported minutes/week of MVPA compared with a wellness contact control group at 6 months and these changes were maintained at 12 months. 19,20 The current study explored the daily physical activity habits of those randomized to the print-based intervention group only.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marcus and colleagues (2007) found that both print- and Internet-based boosters increased PA; however, the study included mostly college-educated, high socioeconomic status, sedentary women. In a recent study with low-active, adult Latinas to determine whether individually-tailored booster materials mailed at 8, 10, and 12 months following a six-month intervention period increased PA at 12 months, Marcus et al (2015) noted that the booster intervention group had greater minutes/week of MVPA than the control group at 12-month F/U. Although the findings were promising, one study limitation involved self-reported MVPA, which may be biased with the intervention group overestimating MVPA (Marcus et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These three measures have been used extensively in physical activity research. [21,22] A consumer satisfaction questionnaire used in our past trials [17,23] was adapted specifically to assess the feasibility and acceptability of the current intervention.…”
Section: Methodsmentioning
confidence: 99%